2021
DOI: 10.1029/2020gb006818
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Amazon on the Biological Pump and the Air‐Sea CO2 Balance of the Western Tropical Atlantic

Abstract: The Amazon River strongly modifies the biogeochemistry of the Western Tropical Atlantic (WTA). To disentangle the different mechanisms driving these modifications, we conduct a series of modeling experiments with a high‐resolution regional ocean model (ROMS) coupled to a biogeochemical/ecological model (BEC) that we augmented to include Diatom‐Diazotroph‐Assemblages (DDAs). In our model, the Amazon River increases net primary production (NPP) in the WTA by almost 10%, exceeding the stimulation expected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(99 citation statements)
references
References 86 publications
7
87
1
Order By: Relevance
“…Despite these potential dramatic consequences regionally, our results suggest that open ocean inflows have a very prominent role in supplying global coastal waters with nutrients, as suggested by ocean inflows versus freshwater contributions to the global coastal ocean in Lacroix et al (2021). Inflows from the open ocean have been demonstrated to majorly dictate biogeochemical dynamics in a multitude of coastal regions (Outer North Sea: Mathis et al, 2019; Thomas et al, 2005, North America East Coast: Fennel and Wilkin, 2009, California Current System: Frischknecht et al, 2018; South China Sea: Dai et al, 2013) while others are clearly driven by riverine inputs (Amazon plume: Louchard et al, 2021, Louisiana Shelf: Große et al, 2019, Sylvan et al, 2006), or for which the dominant controls are still debated (East China Sea: Große et al, 2020; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential dramatic consequences regionally, our results suggest that open ocean inflows have a very prominent role in supplying global coastal waters with nutrients, as suggested by ocean inflows versus freshwater contributions to the global coastal ocean in Lacroix et al (2021). Inflows from the open ocean have been demonstrated to majorly dictate biogeochemical dynamics in a multitude of coastal regions (Outer North Sea: Mathis et al, 2019; Thomas et al, 2005, North America East Coast: Fennel and Wilkin, 2009, California Current System: Frischknecht et al, 2018; South China Sea: Dai et al, 2013) while others are clearly driven by riverine inputs (Amazon plume: Louchard et al, 2021, Louisiana Shelf: Große et al, 2019, Sylvan et al, 2006), or for which the dominant controls are still debated (East China Sea: Große et al, 2020; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the wet season, there is a greater influence of the waters from the Amazon River over the western Tropical Atlantic Ocean (Lefèvre et al, 2020;Louchard et al, 2021;Mu et al, 2021). This is coupled with increased precipitation due to the northward displacement of the ITCZ (Ibánhez et al, 2015;Ibánhez et al, 2016;Utida et al, 2019), hence leading to a net pCO 2 drawdown in the NBC-NECC sub-region, although it remains supersaturated with respect to atmospheric pCO 2 .…”
Section: Of 18mentioning
confidence: 99%
“…The annual average net CO 2 flux across the whole region drops considerably from −1.6 to −0.2 mmol m −2 day −1 , when we remove the ARP sub-region. Thus, the waters derived from ARP are responsible for 87% of the CO 2 uptake by the western Tropical Atlantic Ocean, a greater contribution than the 60% showed by biogeochemical models (Louchard et al, 2021). Hence, further observational efforts are needed to broaden our understanding of this biogeochemically complex region, and thus to improve ocean and climate model estimates.…”
Section: Sea-air Co 2 Exchanges In the Amazon River Plumementioning
confidence: 99%
“…The ocean dynamics of the surface current system (e.g., Johns et al, 1998;Salisbury, et al, 2011;Johns et al, 2021) and the large freshwater input from the Amazon River (Liang et al, 2020), coupled with precipitation dynamics (Ibánhez et al, 2015;Utida et al, 2019), also add a biogeochemical complexity to the western Tropical Atlantic Ocean (da Cunha & Buitenhuis, 2013). Such complexity is reflected in the pronounced spatial and temporal variability of the marine carbonate system and particularly in the sea-air CO2 exchanges (Körtzinger, 2003;Cooley et al, 2007;Lefèvre et al, 2010;Valerio et al, 2021;Louchard et al, 2021;Mu et al, 2021). As a result, some sea-air CO2 flux estimates indicate that the western Tropical Atlantic Ocean acted as a net CO2 source region (e.g., Cooley et al, 2007;Valerio et al, 2020;Louchard et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such complexity is reflected in the pronounced spatial and temporal variability of the marine carbonate system and particularly in the sea-air CO2 exchanges (Körtzinger, 2003;Cooley et al, 2007;Lefèvre et al, 2010;Valerio et al, 2021;Louchard et al, 2021;Mu et al, 2021). As a result, some sea-air CO2 flux estimates indicate that the western Tropical Atlantic Ocean acted as a net CO2 source region (e.g., Cooley et al, 2007;Valerio et al, 2020;Louchard et al, 2021). Conversely, other studies revealed a net CO2 sink behaviour, mainly due to the high primary productivity driven by optimal nutrient availability supplied by the Amazon River waters (e.g., Körtzinger, 2003;Lefèvre et al, 2010;Ibánhez et al, 2015;Mu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%